a PERAN ETIKA PROFESI DALAM MENINGKATKAN KUALITAS LAYANAN KONSELING ISLAM DI LEMBAGA PENDIDIKAN - Akhir Pardamean Harahap; Muhammad Yusuf Kamala; Rahmat Ridho Aljaeraa; Hamdal Afgani Dalimunte; Idris; Ismail (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Islamic counseling services in educational institutions play an important role in character building and psychological well-being of students. However, challenges in counselor professionalism and ethics often affect the effectiveness of these services. This article aims to analyze how professional ethics can contribute to improving the quality of Islamic counseling services. Through a qualitative approach with literature study, this article explores the principles of Islamic counselor ethics and their impact on counselor-client relationships, service integrity, and achievement of counseling goals. The results of the study indicate that the implementation of good professional ethics, such as maintaining confidentiality, being fair, and committing to Islamic sharia values, contributes significantly to client trust and comfort. Thus, internalization of professional ethics is a fundamental aspect in building superior quality Islamic counseling services in educational institutions.